Optimalisasi Kinerja Lembaga Zakat, Infak, dan Sedekah melalui Self-Branding pada Media Sosial: Bukti dari LAZIS Jateng Surakarta - Ellija Humaira; Asia Wati (Sekolah Tinggi Agama islam Negeri Majene, 2023)
The use of social media for marketing products of Zakat, Infaq, and Shadaqah Institution (LAZIS) is an effective alternative to promote to the general public, especially in today's society. This research aims to demonstrate the optimization of LAZIS performance in using social media as self-branding. This type of research is qualitative with a content analysis approach conducted at LAZIS Jateng Surakarta. This research reveals that self-branding on social media is used for the purpose of marketing products of LAZIS Jateng Surakarta which is implemented effectively. Dissemination of some LAZIS Jateng Surakarta products or programs can be channeled well to the general public compared to marketing using print media or voice broadcasts.